Oral Health Status of the Institutionalized Elderly in Mangalore City, Karnataka, South India: Extents, Insights and Action - Teenu Thomas; M Aparna; Sharanya Sreekumar; Vijaya Hegde (Journal of Multidisciplinary Dental Research)
Oral diseases are progressive and cumulative across the life span and due to this reason, the oral health of the institutionalized elderly is of concern within the realm of geriatric care. An improvement in oral health among the institutionalized elderly will boost their social life, self-confidence, mastication and nutritional status, thereby bringing a positive outlook. To assess the periodontal status, dental caries experience, prosthetic status, and prosthetic need of institutionalized elderly in Mangalore. A cross-sectional study was conducted to assess the dental caries experience, periodontal status, prosthetic status, and prosthetic needs of 143 elderly individuals living in geriatric homes in Mangalore city. The demographic data, periodontal status, prosthetic status, and prosthetic need was obtained using the WHO Oral Health Assessment Form 1997. Dental caries experience was recorded according to the WHO modified DMFT Index. Descriptive statistics was obtained using SPSS version 16. The mean dental caries experience of the study subjects was 8.80. The presence of supra or sub gingival calculus was noted in 44.8 % of the subjects and the presence of a pathological pocket of 4 mm or more was seen in 32 %. About 33 of the subjects did not require any kind of prosthesis in the upper & lower arch. From this survey of the institutionalized elderly population, it was evident that, half of them had supra or subgingival calculus deposits and more than 76.9 % have one or the other need for a prosthesis. Keywords Edentulousness, Elderly inmates, Old age homes, Oral health